Improvement of NOX Reduction Rate of Urea SCR System Applied for an Non-Road Diesel Engine - Han, Joonsoo; Kim, Taemin; Jung, Haksup; Pyo, Sukang; Cho, Gyubaek; Oh, Youngtaig; Kim, Hongsuk (International journal of automotive technology, 2019)
Urea SCR technology has been widely used to reduce NOx emissions of diesel engines. Despite remarkable development for decades, more advanced control and optimization of urea SCR systems are still required as global NOx emissions standards are expected to become more stringent. This study investigated several influential parameters of urea SCR system to improve NOx reduction efficiency. This study uses a commercialized UWS (Urea Water Solution) supply system and a SCR catalyst which was installed in the exhaust line of a non-road CRDI (Common Rail Direct Injection) diesel engine. From this study, it was found that the low space velocity of SCR catalyst is essential for high NOx reduction efficiency, especially at low temperatures. Early injection of UWS enhances the overall NOx reduction efficiency if UWS injection was carefully controlled to avoid urea deposits. Rich injection of UWS with AOC is a good strategy for high NOx reduction efficiency. However, NOx reproduction in the AOC, which has an adverse effect on the overall NOx reduction rate, occurs at high exhaust gas temperatures. System insulation also can improve the NOx reduction efficiency by a few percentage points.